ANALYSIS OF AERONAUTIC LANGUAGE INTERACTION - Petrashchuk, Olena (Proceedings of National Aviation University (archive), 2018)
The departure point for the research is the statement that conversation analysis (CA) is aimed to uncover the tacit reasoning procedures as well as sociolinguistic competencies underlying the production and interpretation of talk in organized sequences of interaction [1]. It makes CA popular method in the effective discourse study. Considering aeronautical language interaction (ALI) at a macro level, it is obvious that the linguistic investigation of Aviation English should be done in the connective discourse developed by pilot and controller in the ‘ground-to-air’ talk. Therefore, CA might provide initial knowledge of the radiotelephony exchanges between pilot and controller in that specific context. The aim of this article is to look at CA as a method to describe conventional interactions in radiotelephony through prism of conversation features of general language conventions. To know more about conversation features of RLC can contribute to flight safety associated with language related human factor.